Niveles séricos de apolipoproteínas AII y CIII en individuos con sobrepeso y obesidad del Cercado de Lima - Hernández, Luz K. (2023)
Overweight and obesity are global public health problems that lead to a scenario of alterations in the concentration of circulating lipoproteins; in this scenario, the least studied apoAII and apoCIII have potential as predictors of stroke. The aim of the present study was to determine the levels of apolipoproteins (apoAII and apoCIII) under conditions of overweight and obesity. For this purpose, blood samples were taken from 72 volunteers of both sexes with an age range between 24 and 64 years who were overweight or obese with a body mass index (BMI) greater than 25 kg/m2; additionally, lipid profile, glucose, serum levels of apoAII, apoCIII, insulin, and glycosylated hemoglobin were determined using specific kits following the manufacturer’s instructions. As a result, the average age was 47.3 years, 44.44% were obese, 34.72% were overweight and 20.83% had a normal BMI, with p=0.117, also, statistical differences were observed between groups with respect to glycosylated hemoglobin of 5.72 ± 1.02 % (p<0.039) and insulin 16.2 ± 10.7 mIU/L (p<0.006); in the group of patients with obesity the mean HDL (43.6 ± 11.6) was lower than the mean of the groups (45.8 ± 13.1) and was related to an elevated mean (2.67 ± 0.62) of apoAII without statistical significance (p=0. 222), in contrast to apoCIII (1.21 ± 1.18b,p=0.028). We conclude that apoAII levels do not show statistically significant variation when comparing groups of overweight and obese patients; however, apoCIII does show variations and/or intergroup differences.